Número mínimo de aplicações de fungicidas no controle das cercosporioses da cultura do amendoim - Ruas, Anderson Robert [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The early and late leaf spot in peanut crop are responsible for an important economic damage. Represents by Cercospora arachidicola and Cercosporidium personatum, the early and late leaf spot can occasion production damages in the peanut crop between 50 – 70 %. Among the control measure, the use of contact and systemic fungicide are important. Currently, the sprays are previous established on a set 14 – 15 days schedule, beginning in the 20-30 days after the plants emerge. The previously established of fungicides application has generate a huge problems, related to the bad positioning and the use of fungicides, like in the wrong moment of application, or in the absence in fundamental moment to the control of the disease. It was evaluated the efficiency and a minimum number of fungicides applications in the control of early and late leaf spot in peanut crop. The fungicides evaluated were chlorothalonil, epoxiconazol + pyraclostrobin in the dosages of 4 ml and 2.4 ml/L, applied over 15 days, in field condition located in Jaboticabal and Ibitinga, state of São Paulo . Fungicides were applied using a CO2 pressurized backpack sprayer, and flow of 250 L of spray per hectare. It was adopted the randomized block design, with 6 treatments and 4 repetition. Each sample unit corresponded to an area of 22.5 m2. The variable evaluated were severity of early and late leaf spot symptoms, numbers of leaf scars, fresh weight of stem and grain weight, held on a date of 20/03/2014, in Jaboticabal, and 23/04/2014, in Ibitinga, the evaluation of grain mass held in date of 30/03/2014, in Jaboticabal, and 30/05/2014, in Ibitinga. Through of the data were used exploratory multivariate analyzes by hierarchical clustering method, processed with the Euclidean distance as a measure of similarity between samples, and Ward as the method of connection groups. It was concluded that there is need for at least five applications ...

As cercosporioses na cultura do amendoim são responsáveis por importante dano econômico. Representadas pela mancha castanha causada por Cercospora arachidicola e a mancha preta causada por Cercosporidium personatum, as cercosporioses podem acarretar perdas de produção na cultura do amendoim entre 50 a 70%. Dentre as medidas de controle destacam-se o uso de fungicidas de contato e sistêmicos. Atualmente são empregadas pulverizações pré-estabelecidas, espaçadas entre 14 -15 dias, iniciando-se a partir dos 20-30 dias após a emergência das plantas. O pré-estabelecimento das aplicações tem gerado inúmeros problemas, relacionados ao mal posicionamento e uso dos fungicidas, como aplicações em momentos inadequados, ou ausência em momentos fundamentais para o controle das doenças. Nesse estudo foi avaliado a eficiência e número mínimo de aplicações de fungicidas no controle das cercosporioses da cultura do amendoim. Para tal, foram avaliados os fungicidas clorotalonil, epoxiconazol + piraclostrobina nas dosagens 4 mL e 2,4 mL/L, aplicados em intervalos de 15 dias, em condições de campo, em plantios localizados em Jaboticabal e Ibitinga, estado de São Paulo. Os fungicidas foram aplicados mediante pulverizador costal pressurizado a CO2, e vazão de 250 L de calda por hectare. Adotou-se o delineamento de blocos casualizados, com 6 tratamentos e 4 repetições. Cada unidade amostral correspondeu a uma área de 22,5 m2. As variáveis avaliadas foram severidade de sintomas das cercosporioses, número de cicatrizes foliares, massa fresca das hastes, realizadas em DATA 20/03/2014, em Jaboticabal, e 23/04/2014, em Ibitinga, a avaliação de massa de grãos realizadas em DATA 30/03/2014, em Jaboticabal, e 30/05/2014, em Ibitinga. Os dados foram submetidos a análises multivariada de agrupamento por método hierárquico, processada com a distância euclidiana como medida de semelhança ...
Keywords: Amendoim; Fungicidas; Cercospora; Oilseeds